Establishment and evaluation of nomogram model for risk of PICC related upper extremity deep vein thrombosis in elderly patients (高龄患者PICC导管相关性上肢深静脉血栓发生风险的列线图模型构建与评估) - YAN Ying (闫影); QI Xiaojiu (齐晓玖); SU Qian (苏倩); WANG Pei (王培) (Association of Integrative Nursing, 2022)
Objective To establish a nomogram predicting model for assessing the risk factors of peripherally inserted central catheter (PICC) related upper extremity deep venous thrombosis (DVT) in elderly patients, and to evaluate the discrimination and consistency of the model. Methods The clinical data of 362 elderly patients with PICC in researched hospital from January 2014 to December 2019 were retrospectively analyzed by self-design questionnaire. The incidence of catheter-related upper extremity DVT was calculated. Research subjects were divided into DVT group and non DVT group. The risk factors related to upper extremity DVT occurrence were screened by Logistic regression model, and the risk factors were included in R software to construct the risk factors of upper extremity DVT. The discrimination and consistency of the prediction model were evaluated by ROC curve and goodness-of-fit test. Results The incidence of upper extremity DVT in elderly patients over 80s with PICC was 20. 44% (74/362). The results of Logistic regression model showed that the age, malignant tumor, D-D level before catheterization and operation history during catheterization were independent risk factors for upper extremity DVT in elderly patients with PICC (P<0. 05); The risk factors affecting the occurrence of PICC related upper extremity DVT in elderly patients were introduced into R software (R3. 6. 3) rms package to establish nomogram prediction model, the area under the ROC curve was 0. 777, the slope of calibration curve was close to 1, and the Hosmer-Lemeshow goodness-of-fit test showed χ2=9. 637, P=0. 291. Conclusion The nomogram model based on the risk factors of PICC related upper extremity DVT in elderly patients has good discrimination and consistency, which has certain clinical guiding value for the prevention of upper extremity DVT in elderly patients with PICC. (目的 通过筛选高龄患者经外周静脉穿刺中心静脉置管(PICC)相关性上肢深静脉血栓(DVT)发生的危险因素, 建立列线图预测模型, 并评估模型的区分度与一致性。方法 采用自制调查表回顾性分析2014年1月-2019年12月医院收治的PICC置管高龄患者362例临床资料, 统计导管相关性上肢DVT发生率。根据是否发生上肢DVT分为DVT组与非DVT组, 采用Logistic回归模型筛选影响上肢DVT发生的危险因素, 将危险因素纳入R软件构建预测上肢DVT发生风险的危险因素, 通过ROC曲线与拟合优度检验评估预测模型的区分度与一致性。结果 PICC置管高龄患者上肢DVT发生率为20. 44%(74/362); 纳入Logistic回归模型中, 分析结果显示, 年龄、合并恶性肿瘤、置管前D-D水平、置管期间手术史是影响高龄PICC置管患者上肢DVT发生的独立危险因素(P＜0. 05); 将影响高龄患者PICC导管相关性上肢DVT发生的危险因素引入R软件(R 3. 6. 3) rms程序包建立列线图预测模型, ROC曲线下面积为0. 777, 校准曲线斜率接近1, Hosmer-Lemeshow 拟合优度检验χ2=9. 637, P=0. 291。结论 基于高龄患者PICC导管相关性上肢DVT发生的危险因素建立的列线图模型区分度与一致性良好, 对预防高龄PICC置管患者发生上肢DVT具有一定的临床指导价值。)